Long-Term Outcomes of Fistula First Initiative in an Urban University Hospital—Is It Still Relevant?. (April 2017) - Greenberg, Jacques; Jayarajan, Senthil; Reddy, Sridhar; Schmieder, Frank A.; Roberts, Andrew B.; van Bemmelen, Paul S.; Lee, Jean; Choi, Eric T.
Purpose: Dialysis access failure is a major cause of morbidity in patients with end-stage renal disease. The Fistula First Breakthrough Initiative (FFBI) dictates arteriovenous fistulae (AVFs) should be preferred over arteriovenous grafts (AVGs) as first line for surgically placed accesses. The purpose of this study was to compare patency rates of surgical dialysis accesses in our mature, urban population after the FFBI. Methods: Current dialysis patients with accesses placed between 2006 and 2011 were included. Patient characteristics, access outcomes, interventions, and survival outcomes were analyzed. Results: We report outcomes of 220 patients undergoing dialysis access. Of those 220, 75 received numerous accesses. All outcomes are evaluated as per access itself, that is, a patient may have numerous access types, each individually analyzed. Of the accesses, 138 were AVF and 190 were AVG. The average age of patients was 59.8 years. The groups were evenly matched in distribution of race and prevalence of hypertension, diabetes, coronary artery disease, and Peripheral Vascular Disease (PVD). Average number of complications requiring intervention per access were fewer with AVF than AVG (1.21 vs 1.72, P = .02). The AVF had greater rates of stenosis (51.4% vs 40.6%, P = .0182), whereas AVG had greater thrombosis rates (14.6% vs 31.9%, P < .001). Both AVF and AVG had similar primary patency (median: 186 vs 142 days, P = .1774) and 3-year secondary patency (59.2% vs 49.2%, P = .0945). Arteriovenous fistula in patients aged <60 years was found to have the greatest primary ( P = .0078) and secondary patency ( P = .0400). Outcomes did not differ between AVF and AVG in those aged >60 years. Conclusions: Although complications requiring intervention are greater with AVG, primary and secondary patency rates are similar between AVF and AVG, except when considering AVF in patients aged <60 years.